48.0k views
1 vote
1
Prove that
1: sin/1-cot + cos/1-tan=cos+sin​

1 Answer

6 votes

Answer:

have:


(sin)/(1-cot)+(cos)/(1-tan)\\\\=(sin)/(1-(cos)/(sin) )+(cos)/(1-(sin)/(cos) )\\\\=(sin^(2) )/(sin-cos)+(cos^(2) )/(cos-sin) \\\\=(sin^(2) )/(sin-cos)-(cos^(2) )/(cos-sin)\\\\=(sin^(2)-cos^(2) )/(sin - cos)\\\\=((sin-cos)(sin+cos))/(sin-cos)\\\\=sin+cos

Explanation:

User Thats
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.